Red Blood Cell Morphology in Diabetic Patients: A Case-control Study - Anmol Taneja; Miheer Jagtap; Samarth Shukla; Sunita Vagha (Journal of Clinical and Diagnostic Research, 2022)
Introduction: According to earlier studies, patients suffering from diabetes frequently experience haematological changes. India is the diabetes capital, with 69.1 million residents suffering from the disease. Aim: To study Red Blood Cell (RBC) morphological changes and grading on percentage of cells that differ in size and shape from normal erythrocytes in diabetic patients. Materials and Methods: The case-control study was conducted at Division of Central Clinical Laboratory in Department of Pathology in coordination with Department of General Medicine at Jawaharlal Nehru Medical College, Wardha, Maharashtra, India, from October 2019 to October 2021. Total 90 known cases of diabetes mellitus, aged between 18-80 years and 90 subjects (control group) with normal blood glucose levels were included for the study. Demographic details, anthropometric, parameters i.e, Fasting Plasma Glucose (FPG), Random Blood Sugar (RBS), Glycated haemoglobin (HbA1c) and morphology of blood smear were assessed. Results: The mean age of study group was 54.98±2.31 years and control group was 50.45±17.94 years (p-value= 0.0004). The mean random blood sugar of study group was 163.92±91.31 mg/dL and of control group was 96.92±22.31 mg/dL (p-value=0.0001). Mean HbA1c for the study group was 7.73±1.71%, while in control group was 5.24±0.62% (p-value=0.0001). In the study group, 9 (10%) cases showed a slight anisocytosis (1+) and 3 (3.3%) cases showed moderate anisocytosis (2+), 2 (2.2%) cases showed marked anisocytosis (3+) (variation in size of RBCs with respect to normal) in respect to Mean Corpuscle Volume (MCV), and 11 (12.2%) cases showed MCV <80 fL, 2 (2.2%) cases showed MCV >80 fL, while majority of the cases; 77 (85.5%) had normal sized RBCs, had MCV between 80-99 fL. Conclusion: The findings of the study suggest that there is need for some simple and effective techniques like ectocytometry, micropore filtration for routine haematological tests in type 2 diabetes mellitus.